Public Participation and Legal Awareness: A Literature Review of the Relationship between Rights and Obligations in the Digital Era - Dhiya Ulha’ Habibi Santoso; Abdillah Devan Pamungkas (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to analyze the relationship between Digital Public Participation (Right of Expression) and Legal Awareness in the context of the ITE Law and the PDP Law in Indonesia. Using a Systematic Literature Review and Thematic Synthesis of 20 articles, it was found that digital participation remains ineffective due to low literacy and infrastructure constraints. Furthermore, there are contradictory perceptions of the ITE Law: on the one hand, it is considered to create cybersecurity, but on the other hand, it is criticized for restricting freedom of expression. A balance between digital rights and obligations has not been achieved, as evidenced by the rampant cases of privacy violations due to negligence on the part of data controllers and a lack of public awareness. Therefore, this study concludes that the key to realizing intelligent and responsible participation is through strengthening the concept of Digital Citizenship, which balances literacy, ethics, and legal compliance.